(untitled) (Research, Society and Development, 2025)
Purpose: To revalidate the content of the “Screen Time in Childhood” (STC) instrument. Methodology: The STC instrument contained 24 questions (nine in the first part and 15 in the second part) and was evaluated by five judges with experience in child development and development of structured instruments. Using an evaluation script, different questions related to clarity, cohesion, filling items, forms of response, suitability for the target audience and aesthetic aspect were analyzed. The calculation of the Content Validity Index (CVI) was used to evaluate agreement between judges and the data were analyzed quantitatively (absolute frequency and simple percentage) and qualitatively (content analysis). Results: Among the judges, the majority were speech therapists (80%), graduated between 2003 and 2020, with master’s (60%) and doctorate (40%) degrees, all of whom (100%) had experience in clinical care for children. The results indicated CVI values of 1.0 (100%) in all evaluated items. New questions were proposed (six in total) and response formats (inclusion of the “sometimes” option), accepted by the authors. After validation, the current instrument has 30 questions (nine in the first part and 21 in the second part). Conclusion: The STC showed positive results in its content revalidation, indicating that it is a valid instrument for checking screen time in childhood, and can be used by professionals working in the area of child development.